REM’s role in complying with the rules on commercial and political advertising - Lazarevic, Sofija (CM: Communication and Media ISSN 2466-541X; 2466-5452 (Online), 2025)
In this paper, we will present the role played by the Regulatory Autority for Electronic Media of the Republic of Serbia (REM) in complying with the rules on commercial and political advertising. At the very beginning of the work, we will present the legal framework, i.e. the legal basis on which the functioning and work of REM rests. This legal framework consists of several laws, of which the Law on Electronic Media and the Law on Advertising are certainly the most important. According to the Law on Electronic Media, REM should be, i.e. function as an independent and independent regulatory organization that, in a manner appropriate to a democratic society, implements policies in the field of providing media services, protects freedom of opinion and expression and public interest in the field of electronic media, among other things. However, many professional organizations, the interested public, citizens’ associations and participants in political life in our country have been expressing various criticisms of the aforementioned regulator’s work for a number of years. We will present these remarks in detail in the second part of the paper. At the very end of the work, we will try to make an objective and impartial conclusion about the quality of the work of the Regulatory Autority for Electronic Media with a special emphasis on non-compliance with the rules in commercial and political advertising.